An analysis of selected aspects relating to failure of black businessmen and subsequent leasing of their shop to foreign owners in rural areas in the Greater Letaba Municiplity area of the Limpopo Province: an exploratory analysis approach - Senyolo, Thomas Jeffrey Manjaro (University of Limpopo, 2011)
The leasing out of the shops to foreign owners in the rural areas in Greater Letaba Municipality by black businessmen is of concern to those involved in the economic development of the municipality. An exploratory business analysis approach was used to analyze this report. The previous local shop owners and foreign shop owners were interviewed to get the aspects that made the former fail to successfully run their business. The problem statement and objectives of the research are outlined by comparing the three shop owners through tables, and this paved the way for the researcher to understand different models used to run their businesses. Both local and foreign shop owners used the pricing strategy though their price differed. The foreign shop owners, present local shop owners and previous shop owners have, in terms of management been dealing with pricing, competition and system and equipment. The analyses of findings are presented also in the form of tables. The present local shop owners and foreign shop owners operate more or less the same. They network and buy more stock in order to sell it cheaper. The recommendation and conclusions will assist businesses not to fail in future.
Thesis (MBA) --University of Limpopo, 2011
Keywords: Bussiness; 658.1660968; Business; Business enterprises, black; Small business -- South Africa -- Management